Penerapan Model Pembelajaran Core dalam Meningkatkan Hasil Belajar Siswa Mata Pelajaran IPS Terpadu Kelas VIII SMP Negri 4 Gunungsitoli - Zebua, Nova Berkat; Lahagu, Arianto; Telaumbanua, Wahyutra Aldiman; Laoli, Bezisokhi (AKADEMIK: Jurnal Mahasiswa Humanis, 2024)
This study aims to explore the application of the CORE (Connecting, Organizing, Reflecting, Extending) learning model in improving student learning outcomes in Social Studies subjects at SMP N 16 Kerinci. Based on preliminary data, there is a problem of low student engagement and inadequate academic achievement. The theoretical foundation used includes constructivism theory that supports active student involvement in the learning process. This study used a quasi-experimental method with a pretest-posttest control group design. The research instruments included learning outcome tests and student learning activity observation sheets. Data were analyzed using descriptive and inferential statistical analysis techniques. The results showed that the application of the CORE model significantly improved students' learning outcomes compared to the conventional method. Data analysis also showed an increase in student learning activities, especially in the aspects of engagement and reflection on the material learned. The discussion of the research results indicates that the CORE model is effective in promoting students' concept understanding and critical thinking skills. The conclusion of this study confirms the importance of implementing innovative learning models such as CORE in improving the quality of learning in schools. This research provides practical contributions for teachers in designing more effective learning strategies, as well as opening opportunities for further research on the application of constructivism-based learning models in the Indonesian educational context.